CONTINUITY AND CHANGE IN INDIA’S FOREIGN POLICY IN THE 21ST CENTURY - Anwer, Md. Tarique; Choudhary, Saroj; Neeraj, Dharmendra Kumar; Singh, Surendra; ChandraPrakash; Ahmad, Shakil (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The dynamic interaction between continuity and change that characterizes India's foreign policy in the twenty-first century is influenced by shifting global power structures, changing economic objectives, and new security threats. There has been a discernible change in the tactics and approaches used, even though the fundamental ideas of its post-independence strategy—such as strategic autonomy, non-alignment (now reinterpreted), peaceful coexistence, and dedication to multilateralism—continue to direct its external engagements. Moving from classical non-alignment to a multi-alignment strategy, India has increasingly embraced a flexible and pragmatic approach, interacting concurrently with key global powers such as the United States, Russia, and regional organisations in the Indo-Pacific. With increased trade ties and global economic integration bolstering India's international status, economic diplomacy has emerged as a key pillar. At the same time, a more forceful and proactive foreign policy posture has resulted from growing security concerns, especially those pertaining to regional instability and cross-border terrorism. This change is explained by theoretical stances like constructivism, liberalism, and realism, which emphasize the harmony of identity, cooperation, and power politics. This study shows how India has successfully combined its traditional values with modern strategic needs, and it is backed by statistical measures such as trade growth, defence spending, and diplomatic outreach. In the end, India's foreign policy demonstrates a delicate balancing act to strengthen its position as an emerging global power—maintaining continuity while welcoming necessary change.